Embedding Quality and Safety in Otolaryngology–Head and Neck Surgery Education. (May 2015) - McCormick, Michael E.; Stadler, Michael E.; Shah, Rahul K.
Education in patient safety (PS) and quality improvement (QI) helps both medical students and residents understand the health care environment in the United States, where these concepts are now incorporated into virtually every aspect of patient care. The Accreditation Council of Graduate Medical Education has made PS/QI a mandatory component of resident education, and a number of specialties have published their experiences with incorporating PS/QI into their training programs. In otolaryngology–head and neck surgery, a strong curriculum can be built by teaching residents about the principles of PS/QI through both didactic and experiential learning, and morbidity and mortality and QI conferences can serve as the cornerstone of this curriculum. Understanding the potential challenges in PS/QI education can allow training programs to plan their strategy effectively for successful incorporation into their existing curricula.